Benefits and risks of spontaneous pushing versus directed pushing during the second stage of labour among women without epidural analgesia: A systematic review and meta-analysis. (October 2022) - Yao, Jiasi; Roth, Heike; Anderson, Debra; Lu, Hong; Li, Xianying; Baird, Kathleen
Abstract: Objective: The aim of this systematic review and meta-analysis was to assess the benefits and risks of spontaneous pushing and directed pushing used by labouring women without epidural analgesia during the second stage labour. Design: Systematic review and meta-analysis. Methods: Randomised controlled trials published in PubMed/ MEDLINE, CINAHL, Web of Science, Scopus, EMBASE, psycINFO, the Cochrane Library, and four Chinese databases were systematically searched from their inception to December, 2021. Grey literature were also searched. Two authors independently screened the literature and evaluated the quality of the included studies. Results: Ten studies with a total of 1510 women were pooled. Spontaneous pushing in the second stage of labour reduced the rates of Caesarean section and extended episiotomy. The difference was significant among spontaneous pushing group and directed pushing group, with relative risk and 95% confidence intervals of 0.42 and 0.19–0.94, 0.49 and 0.29–0.82, respectively. There was no significant difference in the duration of the second stage of labour, rates of spontaneous vaginal birth and newborn outcomes. Conclusion: The results of this meta-analysis demonstrate that spontaneous pushing during the second stage of labour results in at least the same maternal and newborn outcomes, lower Caesarean section rates and lower incidence of extended episiotomy.